2019
DOI: 10.1002/anie.201904890
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Pyrrole Reactivity upon Confinement within a Cyclodextrin Metal–Organic Framework

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…64 Martí-Gastaldo and co-workers also demonstrated the possibility of restricting the growth of polypyrrole by confined oxidation of pyrrole (Py) monomers after encapsulation in Rb-CD-MOF to generate terpyrrole (TPy) charge transfer salts (Figure 2d). 65 Whereas Rb-CD-MOF and Rb-CD-MOFPy behave as insulators (  = 10 -11 -10 -12 S•cm -1 ), Rb-CD-MOFTPy displays a million-fold enhancement of the electrical conductivity up to 5•10 -6 S•cm -1 . More recently, Ballav and co-workers polymerized PEDOT and PPy inside the pores of UiO-66.…”
Section: Infiltration Of Conductive Guestsmentioning
confidence: 99%
“…64 Martí-Gastaldo and co-workers also demonstrated the possibility of restricting the growth of polypyrrole by confined oxidation of pyrrole (Py) monomers after encapsulation in Rb-CD-MOF to generate terpyrrole (TPy) charge transfer salts (Figure 2d). 65 Whereas Rb-CD-MOF and Rb-CD-MOFPy behave as insulators (  = 10 -11 -10 -12 S•cm -1 ), Rb-CD-MOFTPy displays a million-fold enhancement of the electrical conductivity up to 5•10 -6 S•cm -1 . More recently, Ballav and co-workers polymerized PEDOT and PPy inside the pores of UiO-66.…”
Section: Infiltration Of Conductive Guestsmentioning
confidence: 99%
“…During the past decade, CD-MOFs have emerged as a novel class of porous, extended frameworks owing to their robust crystallinity, permanent porosity, and excellent biocompatibility. On account of their ability to absorb guest molecules, including gases, drugs, metal-based nanoclusters, and nanoparticles, CD-MOFs have found applications in templated syntheses of metal-based nanoparticles, adsorption, , sensing, , separations, purifications, gels, electrical memories, drug delivery systems, trapping of highly reactive intermediates, catalyst stabilization, and catalyst supports . The initial discovery of CD-MOFs and the development of the field by us in the beginning, with subsequent contributions from a growing CD-MOF community, show that these inexpensive and biocompatible materials stand a good chance of finding applications in personal and home care, as well as in the food and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…[21,[34][35][36][37][38] Them echanism of an anoconfined polymerization occurring inside aM OF has been very recently interpreted through modeling the electron density obtained in the pores by SCXRD after performing the reaction, allowing the detection of the ionic products formed. [39] It is suggested that the MOF affects the mobility of the substrates and controls the overall reactivity of confined molecules.Inthis work, we aim to push the scope of SCXRD/CSM methods further and directly follow the evolution of asupramolecular aggregate of neutral guest molecules in the pores of aMOF,bythe interpretation of the electron density over as eries of time steps depicting as low dynamic process.Acomplete modeling of all the electron density contained in the pores of MOFs is very rarely done given the problems associated with disorder and thermal motions.H owever,w eh ere demonstrate that it is affordable and highly informative.…”
Section: Introductionmentioning
confidence: 99%